Doa sebagai suatu Bentuk Kehidupan: Klemens dari Aleksandria Melampaui Praktik Ritual - Sendjaja, Hendri Mulyana (Theologia in Loco, 2025)
This article explores Clement of Alexandria’s understanding of prayer by examining the Paedagogos and Stromateis VII as an integrated theological body of work. Using a historical-hermeneutical approach and textual-theological analysis, it argues that Clement views prayer as a formative spiritual habitus that combines self-discipline, relational knowledge, and contemplative stillness. In the Paedagogos, prayer functions as a pedagogical dynamic that shapes desire and cultivates virtue through the Logos’s presence in the rhythms of daily life. In Stromateis VII, prayer is depicted as an ongoing inner conversation with God, marking spiritual maturity through participation in divine life. Consequently, prayer is not merely a ritual practice but an existential transformation that heals and restores personal integrity while deepening the believer’s engagement with love in the world.